Effect of Recitation Method to the Students' Interest and Learning Results - Dwi Cahyadi Wibowo; Friana Friana; Emilia Dewiwati Pelipa (Universitas Cokroaminoto Palopo, 2018)
The purpose of this study is to determine whether there is influence of learning methods of recitation on interests and student learning outcomes on equation of status of citizenship. The research method used is quantitative method. The form of research is quasi experiment with non-equivalent control group design. The population in this study are 46 tenth grade students of Multimedia A and B at SMK Negeri 1 Kelam Permai in 2016/2017 academic year. Data collection tools are test and questionnaire. Final measurements after treatment shows significant differences in student learning outcomes on equality of citizenship between experimental class and control class, based on hypothesis test using T test (t count ˃ t table is 5.71 ˃ 2.02). MANOVA test shows that F count ˃ F table that is 27.00 ˃ 19.00 which mean there is significant influence of student's interest and result of study using recitation method. It can be concluded that the recitation method is effective in improving students' interest and learning outcomes on equality of citizenship.